2020
DOI: 10.1038/s41413-019-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

Autologous fibroblasts induce fibrosis of the nucleus pulposus to maintain the stability of degenerative intervertebral discs

Abstract: Lumbar degenerative disc diseases cause low back pain (LBP). The maintenance of the height and stability of the intervertebral disc (IVD) space is an effective treatment for LBP. The following study evaluated the effects of fibroblast injection on intervertebral disc degeneration (IDD) in a preclinical setting. Compared with the IDD group, the fibroblast treatment group demonstrated effective maintenance of IVD height, reduced endplate degeneration, and improved nuclear magnetic resonance signals and overall h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
(41 reference statements)
0
39
0
Order By: Relevance
“…BMSCs was induced to acquire brotic phenotype by Bleomycin in vitro Our previous research using a cell-based approach have shown that induction of reparative brosis may offer bene cial effects against the progression of disc degeneration [17], and this process is associated with TGFβ signaling pathway. Considering the Bleomycin is an effective trigger to induce the upregulation of TGFβ in lung epithelium cells [24] and have been used in clinical situation before , we tried to use bleomycin combined with the multipotentiality of BMCSs to induce their brotic differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMSCs was induced to acquire brotic phenotype by Bleomycin in vitro Our previous research using a cell-based approach have shown that induction of reparative brosis may offer bene cial effects against the progression of disc degeneration [17], and this process is associated with TGFβ signaling pathway. Considering the Bleomycin is an effective trigger to induce the upregulation of TGFβ in lung epithelium cells [24] and have been used in clinical situation before , we tried to use bleomycin combined with the multipotentiality of BMCSs to induce their brotic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent researches have unveiled that there are some MSCs distributed around the outer AF region and endplate [16]. So from a different perspective that a former approach of our studies by injection of autologous dermal broblast cells into degenerative intervertebral to treat IVDD [17]: We showed that the induction of reparative brosis combined with two essential cells in discs, one is to induce the brotic phenotype of MSCs, and the other is to promote the broblastic-like cell AF cells.…”
Section: Introductionmentioning
confidence: 81%
“…BMSCs was induced to acquire brotic phenotype by Bleomycin in vitro Our previous research using a cell-based approach have shown that induction of reparative brosis may offer bene cial effects against the progression of disc degeneration [20], and this process is associated with TGFβ signaling pathway. Considering the Bleomycin is an effective trigger to induce the upregulation of TGFβ in lung epithelium cells [26] and have been used in clinical situation before , we tried to use bleomycin combined with the multipotentiality of BMCSs to induce their brotic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent researches have unveiled that there are some MSCs distributed around the outer AF region and endplate [19]. So from a different perspective that a former approach of our studies by injection of autologous dermal broblast cells into degenerative intervertebral to treat IVDD [20]: We showed that the induction of reparative brosis combined with two essential cells in discs, one is to induce the brotic phenotype of MSCs, and the other is to promote the broblastic-like cell AF cells.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation